Islamic Finance – from Submission to Global Sustainability - Yusoff, Nik Mohd Hasyudeen (Asian Journal of Accounting Perspectives, 2010)
An essay was written by the Chairman of the Malaysian Institute of Accountants’ Financial Reporting Standards Implementation Committee for Islamic Finance.